Transkulturalizam u postkolonijalnom društvu - Ciglar-Žanić, Janja (2004)
The paper deals with the specificity of meanings of multiculturalism in a society which is distinctly postcolonial. The author claims that the varieties of multiculturalism in distinctive postcolonial societies differ conspicuously from multiculturalism in metropolitan societies. This question is elaborated on the example of several different societies, including Croatian.